TINJAUAN YURIDIS PENGATURAN KESELAMATAN DAN KEAMANAN PENERBANGAN SIPIL INTERNASIONAL DALAM KONVENSI CHICAGO 1944 - Meylisa Veky; Maryati Bachtiar; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The sefety and security of international civil aviation is hampered by avariety of factors, one of which is the outside aircraft itself. The shooting wasbased on the reason that the state must defend its sovereignty against foreignaircraft that violated the provisions of the country's airspace. In the period 1973-2014 there were 9 incidents of shooting of international civil aviation aircraft shotdown by the military Case of Korean Airlines Boeing 747 on the way from NewYork headed to Seoul by Soviet Union hunter aircraft on September 1, 1983 whichwas the basis for amending Article 3 of the Chicago Convention in 1944 and morespecifically Article 3 regulates interception of foreign civilian aircraft that violatethe sovereignty of a country But Article 3 changes to the bus have not beenavoided international aircraft against the shooting of the aircraft that occurred inthe case of Malaysia Airlines and foreign civilian aircraft and Americansuspected drug carrying was one of the cases that occurred after the Pasl 3 busraid, the flow of the shooting again and again the accidental factor, but the lackof spelling or negligenceThis type of research can be classified as normative legal research Legalresearch is carried out by examining library material or mere secondary data.As a results of the research problem, there are the main things that canbe contested. First, the Chicago Convention of 1944 is an old convention whosearrangement must be changed because it is no longer suitable at this time and isconsidered less effective including international civil aviation security and safety.second, a country that has sovereignty over its exclusive air space is one of thefactors that makes it difficult for international law to be implemented when thereare cases of shooting of foreign civilian aircraftKeyword : Chicago Convention 1944–Safety and Security–International CivilConvention